MODEL PENERAPAN CORPORATE SOCIAL RESPONSIBILITY OLEH MULTINATIONAL CORPORATION DALAM PENGATURAN INTERNATIONAL FINANCE CORPORATION (IFC) DAN MULTILATERAL INVESTMENT GUARANTEE AGENCY (MIGA) - Hikmatul Ula (Arena Hukum)
Abstract The research focuses on the legal position of Corporate Social Responsibility by Multinational Corporation in the regulation of the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA) and the implementation model of Corporate Social Responsibility by Multinational Corporation in the regulation of the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA). By using the method of normative research with conceptual and analytical approach, it can be seen that the legal status of CSR in the setting of international law is voluntary norm. But in its development, IFC and MIGA position not only as the voluntary CSR norm but important condition that must be met by each company that will work with IFC and MIGA (obligatory norm). The model of Implementation of CSR in IFC and MIGA can be described in two stages, before the execution of corporate business activities (prevetive action) and after running the corporate business activities (repressive and evaluative action). As a preventive action IFC and MIGA requires every corporation to meet established performance standards particularly in terms of environmental and social. As repressive and evaluative methods, the WBG has a duty CAO institution and its function is to receive complaints and grievances of the people associated with the firm in cooperation with the IFC or MIGA. Key words: implementasi, CSR, WBG, IFC, MIGA, voluntary, obligatory norm